Photoacoustic section imaging with integrating detectors - Paltauf, G.; Nuster, R.; Gratt, S. (ALT Proceedings, 2026)
Photoacoustic  section  imaging  is  a  method  for visualizing  structures  with  optical contrast  in selected  layers  of  an  extended  object.  In  order  to avoid  resolution limitations  that  are  due  to commonly used ultrasound detectors of finite size, we propose  the  use  of  extended,  integrating cylindrical  elements  for  focusing  the acoustic detection  into  the  selected  section.  Two  imaging methods  based  on piezoelectric  and  optical detection  are  presented.  Resolution  limits  and results on zebra fish are demonstrated.